The salt chimney effect: delay of thermal evolution of deep hydrocarbon source rocks due to high thermal conductivity of evaporites. Issue 3 (25th November 2015) - Zhuo, Q. G.; Meng, F. W.; Zhao, M. J.; Li, Y.; Lu, X. S.; Ni, P.
Abstract: Half of the topseals to the world's largest oilfields are evaporites. Rock salt has a thermal conductivity two to four times greater than that of other sedimentary rocks found in oil‐ and gas‐bearing basins. Strong heat conduction through evaporites can increase the geothermal gradient above evaporite deposits, resulting in a positive thermal anomaly and above‐average temperature while simultaneously decreasing the geothermal gradient below evaporites, resulting in a negative thermal anomaly. Most Triassic–Jurassic hydrocarbon source rocks in the Kuqa Basin, western China, are overlain by ~1500‐m‐thick Tertiary evaporites with underlying Cretaceous sandstones and mudstones. Directly measured strata temperatures indicate an obvious break in the steepness of the geothermal gradient above and below Paleogene evaporites, with a significantly steeper geothermal gradient above the evaporites. Simulations of the thermal evolution of source rocks based on data collected from well Kela‐2 indicate that if the thickness of evaporites (mainly rock salt and anhydrite rock) in overlying rocks above source rocks increases compared with the thickness of siliciclastic rocks in the overlying rocks, then strata temperatures and vitrinite reflectance in Jurassic source rocks will decrease accordingly. Our thermal simulations based on the thickness and thermal conductivity of evaporites accurately coincide with previous studies based on homogenization temperatures, hydrocarbon–water contact retrospection, and carbon isotope results from natural gases. The gas generation center located in the Kalasu Tectonic Belt today is also sealed in an evaporite‐related structural trap that formed at this time. Therefore, the speculated natural gas generation times not only correlate with the evaporite‐related structural trap formation, but the calculated maturity of deep source rocks below the evaporites also coincides with current gas reserves. And our studies can help to find the deep oils and gases under thick evaporites.